Microbial responses to membrane cleaning using sodium hypochlorite in membrane bioreactors: Cell integrity, key enzymes and intracellular reactive oxygen species. (1st January 2016) - Han, Xiaomeng; Wang, Zhiwei; Wang, Xueye; Zheng, Xiang; Ma, Jinxing; Wu, Zhichao
Abstract: Sodium hypochlorite (NaClO) is a commonly used reagent for membrane cleaning in membrane bioreactors (MBRs), while it, being a kind of disinfectant (oxidant), may impair viability of microbes or even totally inactivate them upon its diffusion into mixed liquor during membrane cleaning. In this study, we systematically examine the effects of NaClO on microorganisms in terms of microbial cell integrity, metabolism behaviours (key enzymes), and intracellular reactive oxygen species (ROS) under various NaClO concentrations. Different proportions of microbial cells in activated sludge were damaged within several minutes dependent on NaClO dosages (5–50 mg/g-SS), and correspondingly organic matters were released to bulk solution. Inhibition of key enzymes involved in organic matter biodegradation, nitrification and denitrification was observed in the presence of NaClO above 1 mg/g-SS, and thus organic matter and nitrogen removal efficiencies were decreased. It was also demonstrated that intracellular ROS production was increased with the NaClO dosage higher than 1 mg/g-SS, which likely induced further damage to microbial cells. Graphical abstract: Highlights: Cell lysis occurred within initial several minutes at NaClO dosages of 5–50 mg/g-SS. Heterotrophic metabolism was inhibited when NaClO concentration was above 1 mg/g-SS. Key enzymes for nitrogen removal were lowered at NaClO dosage higher than 1 mg/g-SS. Increased production of intracellular ROS was observed in the presence of NaClO.